Denotation of color in Trolls Movie by Mike Mitchell (a Semiotic Study Base on Roland Barthes) - Ririn Kirana; Udayani Permanaludin (CALL, 2020)
This journal concerns symbols in Trolls Movie by Mike Mitchell. This theme was chosen by the author because the author knows that denotation is examined in the science of signs known as semiotics. Semiotics is part of the study of literature, with symbols that can be anywhere and anytime included in a film. Most of all people watch movies as mere entertainment, without paying attention to other things that come from the show, such as denotation. Here, the author intends to explore how many color denotations in a film, because of their unlimited use. Based on the background of the problem above, the writer chose the film from Mike Mitchell, the Troll film to be analyzed as an object of research. There is one problem statement that the writer found. That is the question of color denotation in the film Troll. Of the three problem statements above, it will be analyzed using two-phase significance by Roland Barthes. By using this theory, denotation will emerge on its own.